Getting the most out of a pulse oximeter circuit. - Lim, Daniel Teik Tjun. (2009)
Pulse oximetry has been well researched and developed industrially and there is extensive literature regarding its subject matter. The present main uses of pulse oximetry are in analyzing pulse rate and saturation of oxygen in blood. We aim to obtain other kinds of information from pulse oximeter data, especially the breathing rate, via wavelet analysis. In this project, a customized version of pulse oximeter was built from scratch with the purpose of acquiring relevant electronic and optical knowledge and skills. The project could be divided into 3 sections; namely by its 3 objectives. The first objective consisted of the assembly of the hardware: basic electronic components. The second objective used specially designed LabviewTM software to integrate the circuit into a functional pulse oximeter. Testing, trouble-shooting, calibration were conducted. The third and final objective was the conduction of wavelet analysis studies on the raw data samples using MatlabTM. In summary, most of the objectives were met with the exception of SpO2 measurement due to the limitations of the hardware. Wavelet analysis conducted on the samples revealed the breathing rates. These results raise the opportunities for commercial pulse oximeters to exploit wavelet analysis to measure real time breathing rates. This would in turn benefit medical settings tremendously by replacing cumbersome methods of measuring breathing by automating breathing rates.